Meningkatkan Keterampilan Literasi Melalui Pemahaman Literasi Digital pada Siswa/I SD Satu Atap Kelurahan Layana Indah Kecamatan Mantikulore Tahun 2024 - Moh Nurkholis; Naurah Nadzifah; Rafli Marapil; Armita Armita; Ihdinar Hasyim Gaffar; Agung Wahyudi (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The rapid advancement of digital technology has not been followed by equal digital literacy among elementary school students, especially in areas with limited access. This community service activity focused on increasing students' literacy skills through digital literacy understanding at SD Satu Atap Kelurahan Layana Indah, Mantikulore Sub-District. The objective was to enhance students' ability to access, analyze, and utilize digital information responsibly. The strategy used was participatory learning through socialization, workshops, and direct practice involving both students and teachers. This activity was carried out through classroom action and mentoring. The results show that students gained a better understanding of how to use digital platforms for learning purposes, and teachers improved their ability to integrate technology into their teaching. This program successfully increased students’ enthusiasm and skills in digital learning environments.